2012
DOI: 10.1093/nar/gks766
|View full text |Cite
|
Sign up to set email alerts
|

Diverse control of metabolism and other cellular processes in Streptomyces coelicolor by the PhoP transcription factor: genome-wide identification of in vivo targets

Abstract: Streptomycetes sense and respond to the stress of phosphate starvation via the two-component PhoR–PhoP signal transduction system. To identify the in vivo targets of PhoP we have undertaken a chromatin-immunoprecipitation-on-microarray analysis of wild-type and phoP mutant cultures and, in parallel, have quantified their transcriptomes. Most (ca. 80%) of the previously in vitro characterized PhoP targets were identified in this study among several hundred other putative novel PhoP targets. In addition to activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
120
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 50 publications
(75 reference statements)
4
120
1
Order By: Relevance
“…Allenby et al 19 reported the presence of a 9 nucleotides motif in 150 out of 333 PhoP-ChIP enriched sequences. This motif appear to correspond to core DRus.…”
Section: Genetic Basis Of Phosphate Control Of Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Allenby et al 19 reported the presence of a 9 nucleotides motif in 150 out of 333 PhoP-ChIP enriched sequences. This motif appear to correspond to core DRus.…”
Section: Genetic Basis Of Phosphate Control Of Metabolismmentioning
confidence: 99%
“…In fact, when PhoP binds to the − 35 region of the promoters of PhoP-regulated genes, it acts as an activator by recruiting RNA polymerase to the promoter regions, whereas when it binds to the − 10 regions, or inside the open reading frame, usually it works as a repressor by preventing transcription. [19][20][21] THE pho REGULON: PhoP-REGULATED GENES Transcriptomic studies, footprinting assays and in vivo expression studies with reporter genes allowed the initial identification of about 50 genes, which are regulated by PhoP and form the core of the pho regulon. 17 A list of relevant genes regulated by PhoP is shown in Table 1 and a summary of downregulated and upregulated genes is shown in Figure 2.…”
Section: Genetic Basis Of Phosphate Control Of Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…The regulation of CDA biosynthesis is poorly understood, except some twocomponent systems are characterized as its regulators. AbsA2 and PhoP repress the transcription of cdaR (Sheeler et al, 2005;Allenby et al, 2012), while AfsQ1 activates its transcription via binding upstream of cdaR (Wang et al, 2013). Other regulators, such as AbrA2, AbrC3 and NsdA, have been proved to affect CDA production indirectly (Yepes et al, 2011;Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%